UPAYA MENINGKATKAN KEPUASAN TAMU MELALUI SERVICE ENCOUNTER QUALITY DI KOTA BUKIT INDAH PLAZA HOTEL PURWAKARTA - Pratiwi, Yuri Puspita; Purnama, Ridwan; Novelita, Dewi Pancawati (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
The Hotel is one form of accommodation that supports the tourism activity. Kota Bukit Indah Plaza Hotel a four-star hotel in Purwakarta regency has a decrease at the level of customer satisfaction. To increase the customer satisfaction, Kota Bukit Indah Plaza Hotel implementation the service encounter quality is a focus of the performance of the employees by providing the best quality of service delivery currently underway, in the event of contact between employees and individual guest are referred to as the service encounters quality. The purpose of this study was to determine service encounter quality at Kota Bukit Indah Plaza Hotel, the satisfaction of guest who stayed at Kota Bukit Indah Plaza Hotel, and the effect's service encounter quality of the guest satisfaction. In this study, the independent variable (X) was the service encounter quality that consisted of professionalism, civility, friendliness, and competence, and the dependent variable (Y) was individual guest satisfaction. This type of research was a descriptive and verification. The systematic random sampling technique was used to distribute 100 questionnaires for the respondents. The data were analyzed by using path analysis method. The results showed that the variables of service encounter quality had a significant influence on the individual guest satisfaction.